Conceptual design of remote sensing microsatellite for Martian surface. (17th May 2023) - Rudresh, M.; Preethi, S.; Anjali, A.; Akshaya, S.; Aishwarya, H.
This project aims to develop a remote sensing satellite for observing Mars. Microsatellites will be incompetent to traverse Mars autonomously; hence an alternate fail-proof is to deploy multiple microsatellites using a mothership with adequate fuel. The microsatellite performs its operation in a polar orbit that integrates Mars colour camera and thermal infrared imaging spectrometers as payloads and utilises components off the shelf to serve individual subsystem requirements. The chemical propulsion subsystem utilises a monopropellant employing a 1-N thruster. The power subsystem generates and distributes the necessary power to function efficiently using its 18 solar panels. The communication subsystem enables signal transmission between Earth and Mars through its short and long-range broadcast equipment. The unique structural frame of the microsatellite offers a high strength-to-weight ratio during the entirety of the mission. The microsatellite proposes an opportunity for university students to observe Mars at an economically low cost by employing current technology.